2009
DOI: 10.1603/033.046.0102
|View full text |Cite
|
Sign up to set email alerts
|

Description of the Egg ofOchlerotatus japonicus japonicus(Diptera: Culicidae) Using Variable Pressure Scanning Electron Microscopy

Abstract: The egg of Ochlerotatus japonicus japonicus (Theobald) is described with the aid of variable pressure scanning electron micrographs. The egg is black, cigar shaped, and tapers ventrally. The length is approximately 591 microm and the width is approximately 172 microm. The outer chorionic cells are irregular in shape, either hexagonal or pentagonal, and decrease in size toward the anterior and posterior poles. Ventral tubercles typically range from three to six and contact the chorionic reticulum. Dorsal tuberc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
0
11
1
1
Order By: Relevance
“…j. japonicus and Ae. triseriatus eggs (Haddow et al 2009). We found the distinctions between the two species’ eggs to be somewhat subjective and much less obvious than readily observed larval characters, and hence used the following hatching procedures to estimate viable eggs laid and ensure accurate identification of the targeted species.…”
Section: Methodsmentioning
confidence: 99%
“…j. japonicus and Ae. triseriatus eggs (Haddow et al 2009). We found the distinctions between the two species’ eggs to be somewhat subjective and much less obvious than readily observed larval characters, and hence used the following hatching procedures to estimate viable eggs laid and ensure accurate identification of the targeted species.…”
Section: Methodsmentioning
confidence: 99%
“…j. japonicus is a cold-tolerant species that overwinters primarily in the egg stage (for egg surface characteristics, see 34), but sometimes in the larval stage (4, 5, 41, 50, 93). Bartlett-Healy et al (10) observed that Ae.…”
Section: Phenology and Temperature Tolerancesmentioning
confidence: 99%
“…Aedes japonicus is also a daytime biter of a variety of hosts including humans (Andreadis et al, 2001; Goudarz et al, 2009). LACV has been isolated from A. albopictus eggs and adults (Gerhardt et al, 2001; Haddow et al, 2009; Lambert et al, 2010; Westby et al, 2011) and A. japonicus adults (Westby et al, 2011) in the field. For both species, LACV positive adults have been found at case sites of LACV encephalitis in eastern Tennessee (Haddow et al, 2009, Westby et al, 2011), implicating these species as vectors of human cases in the Appalachian region.…”
Section: Biology Of Lacv Vectorsmentioning
confidence: 99%
“…LACV has been isolated from A. albopictus eggs and adults (Gerhardt et al, 2001; Haddow et al, 2009; Lambert et al, 2010; Westby et al, 2011) and A. japonicus adults (Westby et al, 2011) in the field. For both species, LACV positive adults have been found at case sites of LACV encephalitis in eastern Tennessee (Haddow et al, 2009, Westby et al, 2011), implicating these species as vectors of human cases in the Appalachian region. Laboratory infection and oral transmission rates for A. albopictus may be equal to or greater than those for A. triseriatus (Grimstad et al, 1989; Cully et al, 1992), although disseminated infection (Hughes et al, 2006) and transoviral transmission (Tesh and Gubler, 1975) rates are lower.…”
Section: Biology Of Lacv Vectorsmentioning
confidence: 99%
See 1 more Smart Citation